Bombardier Enables Delivery of Short-Form Bomanins in the Drosophila Toll Response - Lin, Samuel J. H.; Fulzele, Amit; Cohen, Lianne B.; Bennett, Eric J.; Wasserman, Steven A. (Frontiers in Immunology, 2020)
Toll mediates a robust and effective innate immune response across vertebrates and invertebrates. In Drosophila melanogaster, activation of Toll by systemic infection drives the accumulation of a rich repertoire of immune effectors in hemolymph, including the recently characterized Bomanins, as well as the classical antimicrobial peptides (AMPs). Here we report the functional characterization of a Toll-induced hemolymph protein encoded by the bombardier (CG18067) gene. Using the CRISPR/Cas9 system to generate a precise deletion of the bombardier transcriptional unit, we found that Bombardier is required for Toll-mediated defense against fungi and Gram-positive bacteria. Assaying cell-free hemolymph, we found that the Bomanin-dependent candidacidal activity is also dependent on Bombardier, but is independent of the antifungal AMPs Drosomycin and Metchnikowin. Using mass spectrometry, we demonstrated that deletion of bombardier results in the specific absence of short-form Bomanins from hemolymph. In addition, flies lacking Bombardier exhibited a defect in pathogen tolerance that we trace to an aberrant condition triggered by Toll activation. These results lead us to a model in which the presence of Bombardier in wild-type flies enables the proper folding, secretion, or intermolecular associations of short-form Bomanins, and the absence of Bombardier disrupts one or more of these steps, resulting in defects in both immune resistance and tolerance.